Does a policy of earlier induction affect labour outcomes in women induced for postmaturity? A retrospective analysis in a tertiary hospital in the North of England. (July 2017) - Proctor, Anna; Marshall, Paul
Abstract: Objectives: to investigate whether a change in the management of postmature pregnancy to earlier induction affects the length of labour and the induction process. Secondly, to assess the feasibility of the research process to inform a future larger study. Design: a change in management of postmature pregnancy in an NHS hospital in October 2013, from induction at 42 weeks gestation to induction between 41–42 weeks, provided an opportunity to conduct a retrospective analysis. Pre-existing data from the maternity database and casenotes were collected and primary outcomes analysed using the Mann-Whitney test and the Hodges-Lehman confidence interval for differences in medians. Setting: a large city based tertiary referral hospital in the North of England. Participants: 125 women induced before the change in policy were compared with 309 women induced after the change. Measurements: primary outcomes were length of 1st and 2nd stage of labour, overall length of labour, length of induction to established labour and length of induction to birth. Findings: the median overall length of labour for women induced at 42 weeks was 6.5 hours, while for women induced at 41–42 weeks this was 5.2 hours. The difference was not statistically significant ( p =0.15, 95% CI for median difference −0.27 to 1.93 hours) with a small effect size (Pearson's r =−0.08). The median length of induction to birth was 13.6 hours for women induced at 42 weeks and 16.5 hours for women induced at 41–42 weeks. This difference was also not statistically significant ( p =0.14, 95% CI for median difference −7.25 to 1.20 hours) with a small effect size (Pearson's r =−0.13). Key conclusions and implications for practice: This study demonstrated no statistically significant differences in length of labour and induction following a change in the management of postmature pregnancy to earlier induction. A large study is needed to establish definitively the effects of earlier induction on labour outcomes.